Coffee consumption and risk of colorectal cancer in a population based prospective cohort of Swedish women. (1st July 2001) - Terry, P; Bergkvist, L; Holmberg, L; Wolk, A
Abstract : BACKGROUND: The presumed protective effect of coffee consumption on colorectal cancer, which is supported by case control studies, has not been confirmed in prospective cohort studies. Cohort studies are few in number however and often suffer from a small number of cases, limited attention to confounding variables, and a low percentage of heavy coffee drinkers. METHODS: We examined data from a large population based cohort of Swedish women who were free from cancer at the start of follow up, with a wide range of coffee consumption, information on many potentially confounding variables, and a larger number of cases than any previous cohort study of coffee consumption and colorectal cancer. RESULTS: During an average of 9.6 years of follow up of 61 463 women aged 40–74 years, we observed 460 incident cases of colorectal cancer (291 with colon cancer, 159 with rectal cancer, 10 with cancer at both sites). We found no association between coffee consumption and colorectal cancer risk. The risk ratio for drinking four or more cups per day compared with none was 1.04 (95% confidence interval 0.63—1.69; p for trend 0.84). The findings were similar for cancers of the distal and proximal colon and rectum. CONCLUSIONS: The recently published affirmative conclusions regarding the protective effect of coffee consumption may be premature. For patients seeking advice about coffee consumption, the evidence suggests that moderate or even high consumption will probably not influence the risk of colorectal cancer.